(untitled) (Ibrahim Cardiac Medical Journal, 2015)
Background & objective: The interest in functional endoscopic sinus surgery (FESS) in the management of chronic sinusitis is increasing day by day. The proponents of FESS for the treatment of chronic sinusitis claim that it is superior to conventional sinus surgery in the management of the disease, but there are limited studies addressing the issue. The present study was undertaken to make a comparative evaluation between FESS and conventional surgery in the treatment of chronic sinusitis. Materials & Methods: This prospective study was conducted between October 2005 to March 2006 in the Department of ENT and Head-Neck Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), and Dhaka Medical College Hospital (DMCH), Dhaka. A total of 60 patients of chronic sinusitis with failed conservative treatment or chronic sinusitis with polyps admitted for surgical treatment were included. Selected patients irrespective of age and sex were randomly assigned to either FESS (n=30) or conventional surgery (n=30) followed by respective interventions. Baseline clinical characteristics, image findings and outcome variables were studied. Result: Majority of the patients (around 70%) in either group was in their second and third decades of life. Males were a bit higher in the FESS group. Nasal obstruction was the predominant complaints (75%) followed by nasal discharge (68.3%) and headache (66.7%). X-ray of paranasal sinuses showed opacity in maxillary antrum and nasal fossa in 90% and mucosal thickening in maxillary antrum in 58.3% cases. CT scan showed isodense shadow in ethmoid region and nasal fossa (86.7%) with blocked osteomeatal complex (OMC) on both sides (73.3%) and mucosal thickening in maxillary antrum (46.7%). The indications for FESS were chronic sinusitis with ethmoidal polyp (73.3%), while that for conventional surgery was chronic sinusitis alone (56.7%). Majority (83.3%) of the FESS group and two-thirds (66.7%) of the conventional group had unilateral operation. Most (90%) of the FESS group required nasal or antral packing during procedure than that of the conventional group (43.3%) (p<0.001). Complete recovery was significantly higher in the former group (70%) than that in the latter group (40%) (p = 0.047). Shorter hospital stay (up to 2 days) was observed in majority of the former group patients (0.001). In terms of complications, periorbital oedema was appreciably lower and numbness of the cheek was completely absent in FESS group than those in the Conventional group (p < 0.001 and p = 0.005 respectively). Conclusion: Functional endoscopic sinus surgery offers higher success and lower morbidity than conventional surgery in the management of chronic sinusitis with or without polyp. However, proper training is mandatory to acquire proficiency in FESS. Ibrahim Cardiac Med J 2014; 4(1): 16-21